Evenhuis achter de microfoon. Op de achtergrond v.r.n.l. Ginjaar-Maas, Deetman, Van Kemenade - Ruigrok, André,
Evenhuis achter de microfoon. Op de achtergrond v.r.n.l. Ginjaar-Maas, Deetman, Van Kemenade.